Penekanan Perkembangan Penyakit Bercak Ungu pada Bawang Merah oleh Cendawan Mikoriza Arbuskula - Marlina Puspita Sari; Bambang Hadisutrisno; Suryanti Suryanti (Jurnal Fitopatologi Indonesia, 2016)
Arbuscular mycorrhizal fungi (AMF) is known to improve the growth of shallot (Allium cepa var. aggregatum) and strengthen the resistance of plants toward disease infection.  This research aimed to find out the roles of AMF in suppressing the development of purple blotch disease caused by  Alternaria sp. on shallot in Caturtunggal, Sleman, Yogyakarta.  Inoculation of AMF either on fertilization of N, P, K or without fertilization treatment resulted on higher plant height and number of leaves compared to those without AMF inoculation. The plant inoculated with AMF had lower purple blotch disease intensity and disease progression than control and fungicide treatment. The result showed that AMF, in addition to act as the bio-fertilizer, is a potential to be a biocontrol agent.